Martensitic precipitation strengthened steel electrolytic polishing method for EBSD (electron back-scattered diffraction) test

The electrolytic polishing method for martensitic precipitation-strengthened steel enhances EBSD testing by using a perchloric acid alcohol solution and intelligent electropolishing, addressing inefficiencies and cost issues in existing methods to achieve high-quality diffraction patterns and efficient sample preparation.

CN119125202APending Publication Date: 2024-12-13BAOTOU IRON & STEEL (GROUP) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411185568.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Current EBSD sample preparation methods for martensitic precipitation-strengthened steel are inefficient, time-consuming, and require high costs, with low success rates due to varying material strengths and the need for mechanical polishing and wire cutting, while electrolytic polishing faces challenges in parameter calibration.

Method used

An electrolytic polishing method using a perchloric acid alcohol solution with specific concentration and temperature settings, combined with mechanical polishing and intelligent operation of the electropolishing machine, to remove surface stress layers and enhance Kikuchi pattern generation.

Benefits of technology

The method achieves high-quality diffraction patterns with a calibration rate above 96%, reducing preparation time to 10-15 seconds and ensuring sample integrity without corrosion pits, while being safe and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119125202A_ABST
    Figure CN119125202A_ABST
Patent Text Reader

Abstract

The invention discloses a martensitic precipitation strengthened steel electrolytic polishing method for an EBSD test. The martensitic precipitation strengthened steel electrolytic polishing method comprises the following steps that (1) martensitic precipitation strengthened steel is mechanically polished; (2) preparing an electrolytic polishing solution; and (3) electrolytic polishing of the martensitic precipitation strengthened steel. A strurs lectropol-5 type electrolytic polishing machine is used for conducting electrolytic polishing on the martensitic precipitation strengthening steel sample obtained after mechanical polishing; (4) EBSD testing: placing the sample subjected to electrolytic polishing on a sample table, and placing the sample table on an objective table of a scanning electron microscope; an EBSD probe is inserted to collect the morphology of a sample detection area, and a high-quality diffraction pattern image can be observed by clicking any micro area of the detection area. According to the method, the stress layer on the surface of the sample can be effectively removed, high-quality Kikuchi patterns can be generated during EBSD detection, the high analysis rate is obtained, and the microstructure of the martensitic precipitation strengthening steel can be researched conveniently.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sample preparation and detection, and in particular relates to an electrolytic polishing method of martensitic precipitation-strengthened steel for EBSD testing. Background Art

[0002] Martensitic precipitation strengthened steel has high strength, high toughness, good welding performance and excellent corrosion resistance and is widely used in engineering fields such as ships, bridges, and containers. The matrix structure of martensitic precipitation strengthened steel is a multi-scale structure involving lath blocks, lath bundles, and laths. With the continuous development and improvement of detection technology, the backscattered electron diffraction (EBSD) technology is mainly used to analyze the microstructure of the martensitic structure with multi-level organizational structure to improve the comprehensive mechanical properties of the steel matrix.

[0003] At present, EBSD sample preparation methods usually include mechanical sample preparation, ion thinning, and electrolytic polishing. Among them, mechanical polishing requires the rough-ground sample to be polished and polished with different particle sizes. The sample preparation time is long and the efficiency is low. In addition, the sample preparation methods are different for different material strengths, and the sample preparation success rate is low. Ion thinning has a good sample preparation effect, but the sample needs to be cut into 50-80μm thin slices by wire cutting, which has the disadvantages of high sample preparation cost and long time consumption.

[0004] Electrolytic polishing technology has the advantages of short time consumption, high efficiency and the ability to effectively remove the surface stress layer. The concentration of the electrolyte and the polishing parameters (voltage, flow rate, time) are the technical difficulties that determine the calibration rate. Therefore, the present invention proposes an electrolytic polishing method for martensitic precipitation-strengthened steel for EBSD testing, which is used for sample processing before using EBSD technology to test the surface microstructure of martensitic precipitation-strengthened steel. The method can effectively remove the stress layer on the sample surface, is conducive to the generation of high-quality Kikuchi patterns during EBSD detection, and obtains a high calibration rate, so as to analyze and study the organization of martensitic precipitation-strengthened steel. Summary of the invention

[0005] The purpose of the present invention is to provide an electrolytic polishing method for martensitic precipitation strengthened steel for EBSD testing, which is used for sample processing before the EBSD technology is used to test the surface microstructure of martensitic precipitation strengthened steel. The method can effectively remove the stress layer on the surface of the sample, which is conducive to the generation of high-quality Kikuchi patterns during EBSD testing and obtaining a high resolution rate, so as to study the microstructure of martensitic precipitation strengthened steel.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for electrolytic polishing of martensitic precipitation-strengthened steel for EBSD testing, comprising the following steps:

[0008] (1) Mechanical polishing of martensitic precipitation-strengthened steel

[0009] The martensitic precipitation-strengthened steel samples were cut by wire cutting, cleaned by ultrasonic instrument, mechanically ground by sandpaper No. 120, No. 240, No. 400, No. 600, No. 800, No. 1000 and No. 1200, and then polished to mirror surface by metallographic sample polishing machine.

[0010] (2) Configuration of electrolytic polishing solution

[0011] Mixing alcohol and perchloric acid in a volume ratio of 90-94:6-10 to obtain an electrolytic polishing solution;

[0012] (3) Electrolytic polishing of martensitic precipitation-strengthened steel

[0013] The martensitic precipitation-strengthened steel samples after mechanical polishing were electropolished using a Struers Electropol-5 electropolishing machine.

[0014] ① Use deionized water to clean the electrolytic polishing device;

[0015] ② Prepare a 500ml and 100ml standard liquid storage container respectively. Put 500ml of 7-9% perchloric acid alcohol electrolyte in the 500ml container, put the 7-9% electrolyte in the refrigerator for cooling, and put 50ml of alcohol in the 100ml container for cleaning the sample after electrolytic polishing;

[0016] ③After the electrolytic polishing device is cleaned, place 7-9% perchloric acid alcohol inside the container tank of the electrolytic polishing machine, and place 2cm above the sample table. 2 Aperture sample mold;

[0017] ④Set the polishing and corrosion program, select the Hardened steel mode, the electrolyte temperature is 8-20℃, the voltage is 18-20V, and the flow rate is 15-18ml / cm 2 , polishing time 10-15s;

[0018] ⑤ Electrolytically polish the martensitic precipitation-strengthened steel sample using step ④, and immediately place it in a 100 ml alcohol container for cleaning and drying after the electrolytic polishing is completed;

[0019] (4) EBSD test: Place the electropolished sample on the sample stage and then on the stage of the scanning electron microscope. Insert the EBSD probe to collect the morphology of the sample detection area. High-quality diffraction pattern images can be observed by clicking on any micro-area in the detection area.

[0020] 2. The electrolytic polishing method for martensitic precipitation-strengthened steel for EBSD testing according to claim 1, characterized in that the specification of the martensitic precipitation-strengthened steel sample is 10 mm×10 mm×2-5 mm.

[0021] Further, perchloric acid was mixed in a volume ratio of 92:8 to obtain an electrolytic polishing solution.

[0022] Furthermore, the electrolyte temperature was selected to be 10°C, the voltage to be 18V, and the flow rate to be 15ml / cm 2 , polishing time 12s.

[0023] Furthermore, the electrolytic polishing machine is intelligently operated and there is no need to assemble the electrolytic device by yourself. The operation process is simple, convenient and safer. At the same time, it can ensure that the current is more stable during the electrolytic polishing process and obtain a high calibration rate.

[0024] Furthermore, the concentration of the perchloric acid alcohol electrolyte is 8%.

[0025] Compared with the prior art, the beneficial technical effects of the present invention are:

[0026] The present invention provides an electrolytic polishing method for martensitic precipitation-strengthening steel for EBSD testing. After preliminary grinding and polishing, chemical corrosion is not required. After the polished sample is placed in an electrolytic polishing device for polishing, the program polishing machine is set to run intelligently, and the experiment time is automatically stopped after the experiment time is up. The sample preparation process is short and the work efficiency is high. After the electrolytic polishing, the sample is cleaned with alcohol, and the alcohol is highly volatile and can be quickly dried after cleaning. The polishing time is 10 to 15 seconds. The short polishing time can completely remove the stress layer on the surface of the sample after mechanical polishing, and corrosion pits will not appear on the surface due to the long polishing time. At the same time, a high-quality diffraction pattern can be obtained, and the calibration rate is above 96%. The configured electrolyte with a concentration of 8% perchloric acid alcohol is stored in a light-shielding sealed glass bottle and is still effective within 30 days when placed in a refrigerator. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present invention will be further described below in conjunction with the accompanying drawings.

[0028] Figure 1 This is the BS diagram of the aged martensitic precipitation strengthened steel obtained in the embodiment of the present invention.

[0029] Figure 2 They are respectively IPF diagrams of the quenched martensitic precipitation-strengthened steel obtained in the embodiments of the present invention. DETAILED DESCRIPTION

[0030] The present invention will be further described in detail below with reference to specific examples. The examples are merely descriptions of the best mode for carrying out the present invention and do not limit the scope of the present invention in any way.

[0031] Example 1

[0032] Electrolytic polishing method for martensitic precipitation-strengthened steel for EBSD testing according to the present invention

[0033] In the first step, the martensitic precipitation-strengthened steel sample after aging treatment was mechanically polished. The martensitic precipitation-strengthened steel sample with a size of 10 mm × 10 mm × 3 mm was cut by wire cutting, cleaned by an ultrasonic instrument, and mechanically ground with 120, 240, 400, 600, 800, 1000 and 1200 sandpapers, and then polished to a mirror surface on a metallographic sample polishing machine;

[0034] The second step is to prepare the electrolytic polishing solution by mixing alcohol and perchloric acid in a volume ratio of 92:8 to obtain the electrolytic polishing solution;

[0035] The third step is electrolytic polishing of martensitic precipitation strengthened steel

[0036] The mechanically polished martensitic precipitation-strengthened steel samples were electropolished using a Struers Electropol-5 electropolishing machine.

[0037] Further, the electrolytic polishing device is cleaned with deionized water;

[0038] Further, prepare a 500ml and a 100ml standard liquid storage container respectively, wherein the 500ml container is put into 500ml of 8% perchloric acid alcohol electrolyte, the 8% electrolyte is put into a refrigerator for cooling, and the 100ml container is put into 50ml of alcohol for washing the sample after electrolysis;

[0039] Further, after the electrolytic polishing device is cleaned, 8% perchloric acid alcohol is stopped inside the electrolytic polishing grade container tank, and the sample stage is protected from 2cm 2 Aperture sample mold;

[0040] Further, set the polishing and corrosion program, select the Hardened steel mode, the electrolyte temperature is 10℃, the voltage is 18V, and the flow rate is 15ml / cm 2 , polishing time 12s;

[0041] Further, the martensitic precipitation-strengthened steel sample was electropolished using step ④, and immediately placed in a 100 ml alcohol container for cleaning and drying after the electropolishing was completed;

[0042] Step 4: EBSD test: Place the electropolished sample on the sample stage and then on the stage of the SEM. Insert the EBSD probe to collect the morphology of the sample detection area. Click any micro-area in the detection area to observe high-quality diffraction pattern images.

[0043] Example 2

[0044] Electrolytic polishing method for martensitic precipitation-strengthened steel for EBSD testing according to the present invention

[0045] In the first step, the martensitic precipitation-strengthened steel sample after quenching is mechanically polished. The martensitic precipitation-strengthened steel sample with a size of 10 mm × 10 mm × 2 mm is cut by wire cutting, cleaned by an ultrasonic instrument, and mechanically ground by sandpapers of No. 120, No. 240, No. 400, No. 600, No. 800, No. 1000 and No. 1200 successively, and then polished to a mirror surface on a metallographic sample polishing machine;

[0046] The second step is to prepare the electrolytic polishing solution by mixing alcohol and perchloric acid in a volume ratio of 92:8 to obtain the electrolytic polishing solution;

[0047] The third step is electrolytic polishing of martensitic precipitation strengthened steel

[0048] The mechanically polished martensitic precipitation-strengthened steel samples were electropolished using a Struers Electropol-5 electropolishing machine.

[0049] Further, the electrolytic polishing device is cleaned with deionized water;

[0050] Further, prepare a 500ml and a 100ml standard liquid storage container respectively, wherein the 500ml container is put into 500ml of 8% perchloric acid alcohol electrolyte, the 8% electrolyte is put into a refrigerator for cooling, and the 100ml container is put into 50ml of alcohol for washing the sample after electrolysis;

[0051] Further, after the electrolytic polishing device is cleaned, 8% perchloric acid alcohol is placed inside the electrolytic polishing grade container tank, and the protection area on the sample stage is 2 cm 2 Aperture sample mold;

[0052] Further, set the polishing and corrosion program, select the Hardened steel mode, and select the electrolyte temperature of 16, voltage of 20, and flow rate of 15ml / cm 2 , polishing time 10s;

[0053] Further, the martensitic precipitation-strengthened steel sample was electropolished using step ④, and immediately placed in a 100 ml alcohol container for cleaning and drying after the electropolishing was completed;

[0054] Step 4: EBSD test: Place the electropolished sample on the sample stage and then on the stage of the SEM. Insert the EBSD probe to collect the morphology of the sample detection area. Click any micro-area in the detection area to observe high-quality diffraction pattern images.

[0055] The present invention uses a polishing machine for electrolytic polishing, and intelligent operation, such as adjusting the current, voltage and flow rate and other polishing parameters, is more convenient; there is no need to assemble the electrolytic device by yourself, saving time. The electrolytic polishing time is short, more time-saving; the electrolyte concentration is low, safer and has a long service life. And the operation is more convenient.

[0056] Due to its own characteristics, it is difficult to obtain high-quality Kikuchi patterns and EBSD analysis diagrams during electrolytic polishing of martensitic high-strength aged steel, and a large number of experiments are required to find suitable electrolytic polishing parameters. The present invention electrolytically polishes samples in different heat treatment states (quenched state and aged state), and the sample surfaces are smooth and no corrosion pits are found. The calibration rate is above 96%, and the effect is shown in Example 1. Figure 1 BS diagram and Example 2 Figure 2 IPF diagram.

[0057] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for electrolytic polishing of martensitic precipitation-strengthened steel for EBSD testing, characterized in that: The following steps are involved: (1) Mechanical polishing of martensitic precipitation-strengthened steel The martensitic precipitation-strengthened steel samples were cut by wire cutting, cleaned by ultrasonic instrument, mechanically ground by sandpaper No. 120, No. 240, No. 400, No. 600, No. 800, No. 1000 and No. 1200, and then polished to mirror surface by metallographic sample polishing machine. (2) Configuration of electrolytic polishing solution Mixing alcohol and perchloric acid in a volume ratio of 90-94:6-10 to obtain an electrolytic polishing solution; (3) Electrolytic polishing of martensitic precipitation-strengthened steel The martensitic precipitation-strengthened steel samples after mechanical polishing were electropolished using a Struers Electropol-5 electropolishing machine. ① Use deionized water to clean the electrolytic polishing device; (② Prepare a 500ml and 100ml standard liquid storage container respectively. Put 500ml of 7-9% perchloric acid alcohol electrolyte in the 500ml container, put the 7-9% electrolyte in a refrigerator for cooling, and put 50ml of alcohol in the 100ml container for cleaning the sample after electrolytic polishing; ③After the electrolytic polishing device is cleaned, place 7-9% perchloric acid alcohol inside the container tank of the electrolytic polishing machine, and place 2cm above the sample table. 2 Aperture sample mold; ④Set the polishing and corrosion program, select the Hardened steel mode, the electrolyte temperature is 8-20℃, the voltage is 18-20V, and the flow rate is 15-18ml / cm 2 , polishing time 10-15s; ⑤ Electrolytically polish the martensitic precipitation-strengthened steel sample using step ④, and immediately place it in a 100 ml alcohol container for cleaning and drying after the electrolytic polishing is completed; (4) EBSD test: Place the electropolished sample on the sample stage and then on the stage of the scanning electron microscope. Insert the EBSD probe to collect the morphology of the sample detection area. High-quality diffraction pattern images can be observed by clicking on any micro-area in the detection area.

2. The electrolytic polishing method for martensitic precipitation-strengthened steel for EBSD testing according to claim 1, characterized in that: The specifications of martensitic precipitation hardened steel samples are 10mm×10mm×2-5mm.

3. The electrolytic polishing method for martensitic precipitation-strengthened steel for EBSD testing according to claim 1, characterized in that: The perchloric acid was mixed in a volume ratio of 92:8 to obtain an electrolytic polishing solution.

4. The electrolytic polishing method for martensitic precipitation-strengthened steel for EBSD testing according to claim 1, characterized in that: The electrolyte temperature is 10℃, the voltage is 18V, and the flow rate is 15ml / cm 2 , polishing time 12s.

5. The electrolytic polishing method for martensitic precipitation-strengthened steel for EBSD testing according to claim 1, characterized in that: The electrolytic polishing machine has intelligent operation and does not require you to assemble the electrolytic device yourself. The operation process is simple, convenient and safer. At the same time, it can ensure that the current is more stable during the electrolytic polishing process and obtain a high calibration rate.

6. The electrolytic polishing method for martensitic precipitation-strengthened steel for EBSD testing according to claim 1, characterized in that: The concentration of perchloric acid alcohol electrolyte is 8%.

Citation Information

Patent Citations

  • Method for preparing super martensitic stainless steel EBSD sample

    CN112160018A

  • Austenitic stainless steel electrolytic polishing method for EBSD test

    CN112229860A

  • Oriented silicon steel microstructure EBSD sample preparation method

    CN112858357A

  • Electrolysis polishing sample preparation method for cold-rolled oriented silicon steel EBSD

    CN114088502A

  • Cobalt-free maraging steel with double-phase structure and preparation method of cobalt-free maraging steel

    CN114622145A